2020
DOI: 10.17126/joralres.2019.073
|View full text |Cite
|
Sign up to set email alerts
|

Association of the P561T and C422F polymorphisms of the growth hormone receptor gene with facial dimensions.

Abstract: Background: Growth hormone plays a significant role in determining craniofacial morphology. Mutations of its receptor gene might be associated with mandibular prognathism (MP). Purpose: The aim of the current study was to evaluate growth hormone receptor (GHR) gene polymorphisms in relation to facial dimensions. Material and Method: The study enrolled 65 participants with class III profile in MP group and 60 orthognathic control participants. Genomic DNA was extracted from a blood sample from the patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…However, no significant association did not find in males and females (Table 2). These results were consistent to previous studies of Korean, Japanese, Iran, Colombian, and Turkish population 19,29‐32 …”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…However, no significant association did not find in males and females (Table 2). These results were consistent to previous studies of Korean, Japanese, Iran, Colombian, and Turkish population 19,29‐32 …”
Section: Discussionsupporting
confidence: 93%
“…However, other studies 19,32 reported that subjects with major allele homozygote of rs6182 and rs6184 showed the greater mandibular RH than subject with heterozygotes. These inconsistencies may be due to different genotype and allele frequencies in population and sample size.…”
Section: Anb Angle Between Lines Nasion-a-point and Nasionmentioning
confidence: 82%
See 3 more Smart Citations